Organizational Factors Influencing Foreign African Court Interpreting in South Africa - Usadolo, Sam Erevbenagie (Indonesian Journal of Social Research (IJSR), 2024)
Employee performance is influenced by organizational factors that require careful management by the human resource divisions of organizations. The involvement of human resources divisions is essential for managing court interpreters who require specific skills, such as understanding court hierarchies, proceedings, and discourse, remaining neutral concerning their language choices, and coping with hearing about sometimes horrific events without succumbing to secondary trauma. The organizational factors in the South African courtrooms were examined by interviewing foreign African court interpreters, magistrates, prosecutors, and attorneys. Observations of courtroom proceedings complement data collected through interview methods. The data analyzed show that the majority of foreign African court interpreters have employment on a casual rather than permanent basis, and organizational issues such as standardized employment procedures, in-service training, monitoring, induction, and orientation, amongst other factors, still require significant improvement to ensure quality foreign African court interpreting in South African courtrooms. The research contributes to the literature on human resources management of court interpreting. The implications of the findings and the limitations of the study are discussed.